PEMBIASAAN MEMBENTUK PERILAKU SOSIAL PESERTA DIDIK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI (Studi Kasus di SDN 003 Loa Kulu Kutai Kartanegara) - Suwarni, Suwarni (LPPM STKIP PGRI Bandar Lampung, 2020)
Inclusion schools have students with various backgrounds from regular students to students with special needs. However, in school there are still students of SD Negeri 003 Loa Kulu who have poor social behavior and negative attitude to other people at home or at school. The aims of this study is assess the results of habituation to shape the social behavior of students with special needs which include improved character, moral improvement, and increased brotherhood between students carried out at SD Negeri 003 Loa Kulu. This research is the best practice to achieve the indicators of the inclusive education vision. The results showed that the habituation program had succeeded in increasing the social behavior of students with special needs. The results of the habituation activities that of the 30 students with special needs show that up to 100% of the 10 indicators must be achieved. Recommendations that class teachers for inclusive classes should take innovative actions in an effort to shape the social behavior of students with special needs.